2008
DOI: 10.1353/hpu.2008.0013
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization: The Experiences of Rural HIV-positive African American Women

Abstract: This qualitative study explored perceptions and experiences of HIV-positive rural African American women regarding availability, accessibility, and quality of health care and social services. Twenty-two women residing in rural areas of South Carolina were recruited to participate in one of three focus groups. A conceptual model of health services utilization was used to guide the study and served as a framework for coding data. Verbatim transcripts of group discussions were analyzed using content analysis to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…2008;Population council 2006). Similar to other researches (Open Society Institute 2008a, b; Paudel et al 2008;Tull et al 2008;Ezeokana et al 2009;Vyavaharkar et al 2008) where women living with HIV/AIDS have low socio economic backgrounds. Their monthly income is insufficient to meet the costs for treatment of HIV/AIDS-related ailments.…”
Section: Discussionsupporting
confidence: 85%
“…2008;Population council 2006). Similar to other researches (Open Society Institute 2008a, b; Paudel et al 2008;Tull et al 2008;Ezeokana et al 2009;Vyavaharkar et al 2008) where women living with HIV/AIDS have low socio economic backgrounds. Their monthly income is insufficient to meet the costs for treatment of HIV/AIDS-related ailments.…”
Section: Discussionsupporting
confidence: 85%
“…The role that perceived HIV-related stigma and discrimination can play as a barrier to care was an important theme in this study that has been reported in other studies of HIV-infected African American women in the Deep South; in particular, unease about seeking health care from non-HIV providers who may respond negatively when the client discloses his/her HIV serostatus. 14,[47][48][49] Of particular concern were two perceptions revealed in this study: (1) not participating in cervical cancer screening is a way to avoid facing another potential major health problems when already feeling burdened and overwhelmed by living with HIV disease; and (2) choosing not to have sex after being diagnosed with HIV eliminates the risk of cervical cancer. Such beliefs must be addressed in any cervical cancer prevention intervention designed for this target population.…”
Section: (Age 48 No Pap Test)mentioning
confidence: 94%
“…The screening process yielded nine articles that met inclusion criteria. The qualitative designs of the articles were Descriptive Inquiry (Gaskins et al, 2011;Kempf et al, 2010;Konkle-Parker, Erlen, & Dubbert, 2008;Miles, Isler, Banks, Sengupta, & Corbie-Smith, 2011;Moneyham et al, 2010;Vyavaharkar, Moneyham, & Corwin, 2008;Williams, Amico, & Konkle-Parker, 2011), Grounded Theory (Mallory, 2008), and Phenomenology (Phillips, Moneyham, Thomas, & Vyavaharkar, 2011). Finally, the reference pages of included papers were perused without success to find additional articles meeting inclusion criteria for the meta-synthesis.…”
Section: Screening the Articlesmentioning
confidence: 99%
“…Tables 2 and 3 were constructed to organize data into manageable categories of key determinants and nine subcategories: Poverty, Stress, Social Exclusion, Work, Transportation, Unemployment, Social Support, Substance Use, and Health Care. Table 2 includes details regarding influences of social determinants of health extracted from five articles (Gaskins et al, 2011;Kempf et al, 2010;Konkle-Parker et al, 2008;Mallory, 2008;Miles et al, 2011), and Table 3 includes information obtained from four articles Phillips et al, 2011;Vyavaharkar et al, 2008;Williams et al, 2011).…”
Section: Classifying the Findings Of The Articlesmentioning
confidence: 99%
See 1 more Smart Citation